1972
DOI: 10.1111/j.1469-185x.1972.tb00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus Laevis and Developmental Biology

Abstract: Summary 1. Because of the present popularity of Xenopus laevis for research in developmental biology, a review of the literature on this animal has been undertaken which emphasizes the anatomical, physiological and developmental features in which it differs from other anuran Amphibia. The need for caution in generalizing from observations on Xenopus to other vertebrates is stressed. 2. Earlier literature and the use of Xenopus for pregnancy testing have been surveyed briefly. Some of the peculiarities of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 252 publications
0
8
0
Order By: Relevance
“…All specimens were adult, the nose to vent length of males was 58-85 mm (mean 73 mm) and that of females was 63-120mm (mean 90 mm). The age of the toads is difficult to estimate; Deuchar (1972) reported that males stop growing at maturity (two years) but females grow continuously. Comparison of the present specimens with laboratory-raised toads indicates a minimum age for all individuals of about three years and the size of some females suggests an age of at least ten years.…”
Section: The Hostmentioning
confidence: 99%
“…All specimens were adult, the nose to vent length of males was 58-85 mm (mean 73 mm) and that of females was 63-120mm (mean 90 mm). The age of the toads is difficult to estimate; Deuchar (1972) reported that males stop growing at maturity (two years) but females grow continuously. Comparison of the present specimens with laboratory-raised toads indicates a minimum age for all individuals of about three years and the size of some females suggests an age of at least ten years.…”
Section: The Hostmentioning
confidence: 99%
“…This practice persisted through the 1970’s. Though no longer used for pregnancy testing, Xenopus have since become a major animal model in biomedical and basic science research [8]. Significant populations of Xenopus (largely X. laevis and to a lesser extent, X. tropicalis ) are currently housed in research laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the considerable interest in the development of the visual system (see Gaze 1970;Jacobson 1970;Hollyfield 1971;Straznicky & Gaze 1971;Deuchar 1972;Horder & Spitzer 1973;Deuchar 1975;Jacobson 1976a; and reviews by Jacobson 19766 and Keating & Kennard 1976), knowledge about the differentiation of its photoreceptors and pigment epithelium (p.e.) is surprisingly limited (Saxen 1954;Lanzavecchia i960;Dixon & Cronly-Dillon 1972;Grillo & Rosenbluth 1972;Chung, Stirling & Gaze 1975;Witkovsky et al 1976).…”
Section: Introductionmentioning
confidence: 99%